Eligibility for clinical trials is limited for youth with type 2 diabetes: Insights from the Pediatric Diabetes Consortium T2D Clinic Registry. Issue 8 (10th October 2018) - Tamborlane, William V.; Chang, Peiyao; Kollman, Craig; Klingensmith, Georgeanna J.; Ruedy, Katrina; Gal, Robin L.; Van Name, Michelle; Bacha, Fida; Willi, Steven; Beck, Roy W.
Abstract : Background/Objective: Restrictive eligibility criteria have hampered enrollment into trials for new drugs for youth with type 2 diabetes (T2D). We utilized Pediatric Diabetes Consortium (PDC) T2D Registry enrollment data to estimate the percentage of patients who would be excluded from current T2D trials based on out‐of‐range HbA1c levels. We also examined whether well‐controlled patients could be included because baseline HbA1c would rise during a 6 to 12‐month study if assigned to control group. Methods: Clinical characteristics and HbA1c levels were collected from 956 T2D patients aged 10 to <18 years upon Registry enrollment. HbA1c levels were also analyzed in 6‐month intervals during the first 30 months of T2D duration. Results: There was an approximately 2:1 ratio of females to males; the majority were obese and from economically disadvantaged minority families. On enrollment in the Registry, 53% of patients would be excluded from current trials because HbA1c levels were either <6.5% (<48 mmol/mol) (37%) or >10.5% (>91 mmol/mol) (16%). Furthermore, in patients with HbA1c levels <6.5% (<48 mmol/mol) and T2D duration between 6 and 30 months, mean HbA1c levels increased by 0.6% (6 mmol/mol) and 0.9% (10 mmol/mol) over the subsequent 6 and 12 months, respectively. Conclusions: Eligibility criteria for current clinical trials still exclude a large proportion of pediatric T2D patients because of HbA1c levels. Including patients with HbA1c <6.5% (<48 mmol/mol) would enhance recruitment and allow comparisons of the investigational treatment with placebo‐assigned subjects in whom HbA1c levels would on average increase during the 6 to 12 months of the trial.